Авторське тлумачення українізмів у російськомовних творах Г. Ф. Квітки-Основ’яненка - Полякова, Т.М. (Мовознавство, 2017)
У статті проаналізовано способи подання українізмів у російському художньому тексті Г. Ф. Квітки-Основ’яненка. Індивідуально-авторську методику тлумачення інокультурного лінгвокомпонента розглянуто як складову частину змісту твору і як своєрідну рису стилю письменника. The article deals with different possibilities of presenting and interpreting specific Ukrainian words that are proper in the Russian-language literary discourse of the Ukrainian writer H. F. Kvitka-Osnovjanenko. The author’s methodology in rendering the sense of those language components that pertain to a different culture is considered, Kvitka-Osnovjanenko’s style and literary skills are also regarded.